Islam Salafi, Tafsir, dan Politik Penyuntingan - Sunarwoto, Sunarwoto (SUHUF, 2024)
Traditionalists have strongly criticized that the ambition to refer to the Qur’an and sunnah led Salafis to disconnect the intellectual network (isnad) of Islam from the prophet Muhammad. However, a meticulous reading demonstrates that Salafis are far from ignoring the Islamic intellectual heritage of the past produced after the periods of three early generations of Islam (al-salaf). This can be seen in the Salafi scholarly production by editing (tahqiq) and publishing classical Islamic texts. This article is to study Mufradat Alfaz Al-Qur’an (MAQ) by ar-Ragib al-Asfihaniy (d. 1108) edited by Mustafa al-’Adawiy. It aims to elaborate on how Salafi scholarly production has been developed. Methodologically, it utilizes Gerard Genette’s paratextual model. It is argued that the editing of MAQ by al-’Adawiy is an attempt to claim the connection of Salafi Islam with the Islamic intellectual tradition in the past. Moreover, al-’Adawiy’s editing generates a typically Salafi-oriented interpretation, which corrects previous interpretations. This is a kind of “politics of editing.”